2014 IEEE 11th Consumer Communications and Networking Conference (CCNC) 2014
DOI: 10.1109/ccnc.2014.6866604
|View full text |Cite
|
Sign up to set email alerts
|

Network-based distributed mobility management for network mobility

Abstract: Network Mobility (NEMO) Basic Support Protocol (NBSP) provides mobility supports for mobile networks. NBSP is an extension of Mobile IPv6 which employs a centralized mobility management approach. It relies on a static and centralized home agent for signaling management and data forwarding. All data traffic traverses a centralized home agent, which leads to sub--optimal routing, high packet overhead and latency, especially in nested NEMO (i.e. when the mobile networks connect to one another to reach the infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…This solution improved the functionalities of mobility entities and centralized network entities. The mathematical analysis revealed that the packed tunnelling cost and the signalling overhead cost of the FDMA are lower than those of PNEMO (Ryu et al, 2013) and NBSP (Ernest et al, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…This solution improved the functionalities of mobility entities and centralized network entities. The mathematical analysis revealed that the packed tunnelling cost and the signalling overhead cost of the FDMA are lower than those of PNEMO (Ryu et al, 2013) and NBSP (Ernest et al, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…In the dynamic TA planning, there are mainly tracking area planning methods based on time [16], based on movement [17,18], based on distance [19][20][21]. These methods dynamically and flexibly define the size of the TA, and can effectively prevent the occurrence of 'ping-pong' effect, reducing the signalling overhead.…”
Section: Related Workmentioning
confidence: 99%
“…Besides, based on the PMIPv6, Do and Kim [17] combined the LMA and MAG functions into each access router and introduced a proxy router to manage MNs' mobility and set up a central session database to track MNs and the proxy router. Furthermore, Ernest et al [18] improved these schemes by decomposing the logical functions of LMA to location management and resource management. It not only extends LMA to support the home network prefix allocation functions, but also extends MR to support the Delegating Router (DR) and Request Router (RR) functions.…”
Section: Dmm-based Schemes Dmm-related Schemes Applymentioning
confidence: 99%
“…It is worth to note from such application scenarios that the group is one of important characters in IoT [5][6][7]. Therefore, several works have focused on this problem and proposed lots of solutions [8][9][10][11][12][13][14][15][16][17][18][19][20] most of which tried to apply the NEtwork MObility (NEMO) [21] into the IoT.…”
Section: Introductionmentioning
confidence: 99%